PTEN as a prognostic and predictive marker in postoperative radiotherapy for squamous cell cancer of the head and neck. - Miroslaw Snietura; Magdalena Jaworska; Joanna Mlynarczyk-Liszka; Aleksandra Goraj-Zajac; Wojciech Piglowski; Dariusz Lange; Grzegorz Wozniak; Elzbieta Nowara; Rafal Suwinski (PLoS ONE, 2012)
BACKGROUND: Tumor suppressor PTEN is known to control a variety of processes related to cell survival, proliferation, and growth. PTEN expression is considered as a prognostic factor in some human neoplasms like breast, prostate, and thyroid cancer. METHODOLOGY/PRINCIPAL FINDINGS: In this study we analyzed the influence of PTEN expression on the outcome of a randomized clinical trial of conventional versus 7-days-a-week postoperative radiotherapy for squamous cell cancer of the head and neck. The patients with cancer of the oral cavity, oropharynx, and larynx were randomized to receive 63 Gy in fractions of 1.8 Gy given 5 days a week (CF) or 7 days a week (p-CAIR). Out of 279 patients enrolled in the study, 147 paraffin blocks were available for an immunohistochemical assessment of PTEN. To evaluate the prognostic value of PTEN expression and the effect of fractionation relative to PTEN, the data on the outcome of a randomized clinical trial were analyzed. Tumors with a high intensity of PTEN staining had significant gain in the loco-regional control (LRC) from p-CAIR (5-year LRC 92.7% vs. 70.8%, for p-CAIR vs. CF, p = 0.016, RR = 0.26). By contrast, tumors with low intensity of PTEN did not gain from p-CAIR (5-year LRC 56.2% vs. 47.2%, p = 0.49, RR = 0.94). The intensity of PTEN highly affected the LRC in a whole group of 147 patients (5-year LRC 80.9% vs. 52.3% for high vs. low PTEN, p = 0.0007, RR = 0.32). In multivariate Cox analysis, including neck node involvement, EGFR, nm23, Ki-67, p53, cyclin D1, tumor site and margins, PTEN remained an independent predictor of LRC (RR = 2.8 p = 0.004). CONCLUSIONS/SIGNIFICANCE: These results suggest that PTEN may serve as a potent prognostic and predictive marker in postoperative radiotherapy for high-risk squamous cell cancer of the head and neck.